Catalytic hydrogenation products of aromatic and aliphatic dicarboxylic acids - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2019)
Hydrogenation of aromatic dicarboxylic acids gave 100 % selectivity to respective cyclohexane dicarboxylic acid with 5 % Pd/C catalyst. 5 % Ru/C catalyst was observed to give over hydrogenation products at 493 K and at lower temperature (453 K) the selectivity for cyclohexane dicarboxylic acids was increased. Hydrogenation of phthalic acid with Ru-Sn/Al2O3 catalyst was observed to give phthalide instead of 1,2-benzene dimethanol or 2-hydroxy methyl benzoic acid. Ru-Sn/Al2O3 catalyst selectively hydrogenated the carboxylic group of cyclohexane dicarboxylic acids to give cyclohexane dimethanol. Use of proper catalysts and reaction conditions resulted in desired products.

Catalytic hydrogenation of cinnamic acid and salicylic acid - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2020)
Hydrogenation of cinnamic acid and salicylic acid was carried out using 5 %Ru/C, 5 % Pd/C and Ru-Sn/Al2O3 catalyst at 493 K and 6.89 MPa of hydrogen partial pressure. Ru-Sn/Al2O3 catalyst was found to be active for hydrogenation -COOH group to give cinnamyl alcohol. The selectivity to cinnamyl alcohol was low (15 %) as absolute inhibition of C=C bond hydrogenation in cinnamic acid is challenging. 5 %Pd/C catalyst was found to hydrogenate C=C bond and aromatic ring in cinnamic acid. 5 %Ru/C catalyst was found to be least selective catalyst as it hydrogenated C=C bond, aromatic ring and -COOH group in cinnamic acid. Hydrogenation of salicylic acid is not possible at 493 K as decarboxylation of salicylic acid occurs.